Prenatalno diagnosticiranje prirojenih nepravilnosti sečil - Trojner-Bregar, Andreja (Slovenska pediatrija, 2023)
Low-grade gliomas (LGG) are the most common primary tumours in the central nervous system in children. Histologically, they are a heterogeneous group of brain tumours. The most common of them is pilocytic astrocytoma. The signalling pathway of mitogen-activated protein kinase (MAPK) is involved in the pathogenesis of these tumours, so the search for effective targeted drugs with few side effects is the subject of current research. This article presents a clinical case of a boy with inoperable LGG, which was poorly responsive to established systemic treatment, so he received targeted treatment with an MEK inhibitor.
Keywords: congenital anomalies of the kidney and urinary tract; diagnosticiranje; diagnostics; magnetic resonance imaging; masgnetnoresonančno slikanje; prirojene nepravilnosti sečil; ultrasound; ultrazvok